Afery i nadużycia gospodarcze. Przyczynek do badań nad przestępczością w PRL - Romański, Mirosław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The article makes a contribution to the research over that subject matter, both paying attention to history and law. Undoubtedly, the discussed subject matter is one of the most emotional issues connected with history of the Polish People’s Republic. In spite of that there is no full monopraph showing the discussed phenomenon, in a form of a syntetic study. I would be worth taking up such an idea. Preliminary research included the collection of New File Archives in Warsaw, where one can find lots of information on the studied topic. It was supplemented with the press sources, which are the mine of knowledge within that subject, althoug the Author had to be careful and interpret the facts presented there properly. It concerns mainly the numerical data which did not correspond the real actual state at that time. The Propaganda done in party press was mainly aimed the artificial emphasizing of the achievements of the judiciary authorities in battle with malpractice and their successes, not really true. The above subject matter will be widely developed in future, by the majority of historians fascinated with the latest Polish times, both in micro and macro dimension.